Comparative studies on vertical administrative reforms in China and Germany, Juli 2016. - (:unkn) unknown (My University, 2016)
This book has a collection of 31 pieces of research results of Chinese and German experts, scholars and government officials. They are categorized into four sections: 1. Introduction and analysis of the current situation of Sino-German administrative systems, such as experimental units of counties directly under the management of provincial governments in the progress of China's urbanization, comparison of the Sino-German intergovernmental jurisdiction division, history of the German administrative regions and local finance of Germany etc.; 2. Sino-German challenges faced by the administrative systems, such as challenges of reform of counties directly under the management of provincial governments in China, urban-rural imbalance in the progress of modernization of Germany and impacts of population change on local ad-ministration management; 3. Sino-German exploration and experience in administrative reform, such as experience and inspiration of the administrative hierarchy reform of Hainan, China, efficiency and expectation of strategies of "urban-rural integration" in Chengdu, China, inter-municipal cooperation in Germany - design and limits of shared service, multilevel function reformation of Rhineland-Palatinate, Germany; 4. Sino-German strategies of administrative reforms under the financial cri-sis, such as influences of economic and financial crisis on German administration, strategies of China's urban-rural integration and optimization of longitudinal administrative levels under financial crisis, promotion of equivalence of public services with fiscal balance.
Keywords: Verwaltung; Verwaltungsreform; Kommunalverwaltung; Ländlicher Raum; Kommunalrecht; Kommunale Selbstverwaltung; Dezentralisation; Funktionalreform; Gebietsreform; Kommunale Zusammenarbeit; Öffentliche Aufgabe; Rechtsvergleich; Finanzierung; Verwaltungsmodernisierung; Internationaler Vergleich; Verwaltungssystem; Verwaltungsaufbau; Governance; Finanzkrise